Effects of Supplemental Oxygen and Dexamethasone on Surgical Site Infection: A Factorial Randomized Trial. Issue 3 (June 2016) - Kurz, A.; Fleischmann, E.; Sessler, D. I.; Buggy, D. J.; Apfel, C.; Akça, O.
Abstract : (Abstracted from Br J Anaesth, 115:434–443, 2015) Surgical site infection (SSI) is thought to be inversely related to tissue oxygenation during and a few hours after surgery and is associated with chronic steroid use. It is characterized as superficial incisional, deep incisional, or peritoneal.